Development Strategy of Speaking Skill for The Tsanawiyah Level/ استراتيجيات تنمية مهارة الكلام للمرحلة الثانوية - Ahmad Fikri Amrullah; Bakri Muhammed Bakheit; Miftahul Huda (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The intercession of speaking makes us easier to socialize and communicate with other people. This study uses a descriptive qualitative approach with case studies, focusing on learning at Al-Kamal Islamic Boarding School Kunir Blitar and Al-Mawaddah Female Islamic Boarding School 2 Nglegok Blitar, Indonesia. Data collection used three methods in-depth interviews, participant observation, and documentation. Data analysis used the Miles and Huberman method: data collection, data classification, data presentation, and conclusion. The findings of the research: 1) The implementation of strategies used by teachers in developing speaking by creating language organization, designing language learning tools, implementing speaking Arabic in daily activities, evaluating speaking, creating a language environment, and applying continuous monitoring. The strategies used by the teacher in developing kalam include spreading Arabic vocabulary, practicing speeches, reading habits, practicing mahfudzot, learning nahwu and shorof, performing drama, and giving language court contracts. The strategies for developing speaking skills (maharah kalam) will be effective when they are supported by the right approach, an appropriate educational curriculum, an active language environment, and language activities that are interesting and attractive to students.